2013
DOI: 10.1021/ja4032677
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Controlled, Palladium-Catalyzed Intermolecular Amination of Arenes

Abstract: We report the Pd-catalyzed amination of arenes to form N-aryl phthalimides with regioselectivity controlled predominantly by steric effects. Mono-, di-, and trisubstituted arenes lacking a directing group undergo amination reactions with moderate to high yields and high regioselectivities from sequential addition of PhI(OAc)2 as an oxidant in the presence of Pd(OAc)2 as catalyst. This sterically derived selectivity contrasts that for analogous arene acetoxylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
68
0
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(75 citation statements)
references
References 53 publications
3
68
0
4
Order By: Relevance
“…For example, Hartwig and co-workers documented a Pd-catalyzed intermolecular C–H amination reaction of arenes with phthalimide to form N -aryl phthalimides using 6 equiv of PhI(OAc) 2 as an oxidant (eq 1). 9 Similar works reported by Chang et al 10a and DeBoef et al 10b were performed in the presence of PhI(OAc) 2 (2.5–5 equiv) without adding any metal species (eq 2). At the same time, Li et al demonstrated a Rh(III) and Ag cocatalyzed C–H amination of arenes bearing directing groups using N -OTs phthalimide as amidating reagent (eq 3).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…For example, Hartwig and co-workers documented a Pd-catalyzed intermolecular C–H amination reaction of arenes with phthalimide to form N -aryl phthalimides using 6 equiv of PhI(OAc) 2 as an oxidant (eq 1). 9 Similar works reported by Chang et al 10a and DeBoef et al 10b were performed in the presence of PhI(OAc) 2 (2.5–5 equiv) without adding any metal species (eq 2). At the same time, Li et al demonstrated a Rh(III) and Ag cocatalyzed C–H amination of arenes bearing directing groups using N -OTs phthalimide as amidating reagent (eq 3).…”
Section: Introductionsupporting
confidence: 73%
“…Herein, we document a Cu-catalyzed C–H amidation of N -pyrimidyl(pyridyl) indoles and 2-arylpyridines under oxygen using phthalimide as an aminating source (eq 4), which is complementary to the previously reported metal-catalyzed C–H amination systems. 911,1315 …”
Section: Introductionmentioning
confidence: 99%
“…1 Palladium-catalyzed C–H amination methods typically require strong stoichiometric oxidants, such as diacetoxyiodobenzene, 2 oxone,3 or [F + ] sources. 4,5 A common reaction pathway associated with these reactions involves oxidation of an aryl-Pd II intermediate to a high-valent Pd III or Pd IV species, 6 which then undergoes facile reductive elimination of the C–N bond and circumvents the intermediacy of an unstable Pd 0 species (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[6i-k] In addition, af ew reports on iodine(III)-mediated electrophilica ryl amination have appeared in the past few years. [7][8][9] As above,e xcessr eagents and high temperatures are routinelya ppliedi no rder to obtain the desired reactivity.M ore importantly,t he regioselectivity,i fn ot innate, [6h, l] is generally difficult to control, despite the use of additional transitionmetal catalysts, [9c, e] resulting in the isolationo fc omplex mixtures of isomers.…”
mentioning
confidence: 99%
“…This provides the opportunity for complementary deprotection conditions and furtherf unctionalization. Interestingly,w hen acetanilide 1q,b earing a tert-butyl group blocking the para position, was submitted to the reactionc onditions, neither ortho nor meta imidation product could be detected.T his suggests that ad ifferent mode of action than those generally proposed for electrophilica mination processes [6,9] may be operating (see below). Finally,s trong electron-donating (OMe) or -withdrawing (NO 2 )g roups were found to be more problematic, owing to exacerbated or lessened reactivity,l eading to over-oxidized products or recovered starting material, respectively.I ti s, however,w orth mentioning that this iodine(III)-mediated/catalyzed arene CÀNb ond-forming reaction is the first methodt op rovide ad irect access to av aried range of substrates [20] under mild conditions, and with exclusive regioselectivity,t hus avoiding very difficult separations between two or more isomers.…”
mentioning
confidence: 99%